The Influence of Organizational Culture, Work Discipline, and Work Experience on Employee Performance - Yupitasari; Pujiati, Herni (Dinasti Publisher, 2025)
Human resource management plays an active role in improving employee performance through several variables affecting it including organizational culture, work discipline, work experience, and employee performance. The formulation of the problem in this study is whether organizational culture, work discipline, and work experience have a significant effect on PT. Sinarmulia Sukses Makmur. This study is a quantitative study with a descriptive design. The research was conducted by searching for primary data, through the filling out of questionnaires by respondents of employees of PT. Sinarmulia Sukses Makmur, was conducted by sampling through a random sampling method. The data are processed by statistical analysis with multiple linear regression tests, coefficient of determination (R-square adjustment), partial testing hypothesis (t-test), and simultaneous ANOVA testing (F-table). The purpose of this study is: 1) To find out the effect of organizational culture on employee performance. 2) To find out the effect of work discipline on employee performance. 3) To find out the effect of work experience on employee performance. 4) To find out the effect of organizational culture, work discipline, and work experience jointly on the performance of employees. The results of this study are as follows: 1) Organizational culture has a significant effect on employee performance. 2) Work discipline has a significant effect on employee performance. 3) Work experience has a significant effect on employee performance. 4) Organizational culture, work discipline, and work experience jointly have a significant effect on the performance of PT. Sinarmulia Sukses Makmur employee. The conclusion of this study is that there is a significant influence on organizational culture, work discipline, work experience, and employee performance at PT. Sinarmulia Sukses Makmur. Suggestions for subsequent researchers to proceed with follow-up studies that address a wider scope such as adding other variables.